Comparison of endoscopic diagnosis and histopathological results of patients with a preliminary diagnosis of malignancy and the role of the nurse in planning - Topçu, Birol; Vatan, Volkan (Progress in Nutrition, 2020)
Study Objectives: Endoscopy has become a gold standard for the diagnosis, . In these procedures, pathologic help is taken for definite diagnosis. An appointment is made according to the priorities of the patients applying to the endoscopy. In this sense, the role of nurses is important in regulating appointments. Methods: In this study, it was aimed to compare endoscopy results with pathology results of patients who were sent to the endoscopy unit considering the suspicion of cancer in the digestive system. A retrospective study involving 570 patients completed endoscopy between January 2014 and December 2016 was approved. Changes in gastrointestinal system (GIS) hemorrhage, occult blood presence in the stool, Ca height, anemia of iron deficiency, malignancy, hematochezia, colon Ca, lamellar Ca stain, excess weight loss, change in bowel habit, wall thickening in the gastrointestinal tract or mass-indicating signs in radiological tests were considered criteria for cancer pre-diagnosis. Results: Of the 368 patients with upper gastrointestinal endoscopy, 18 (4.9%) were diagnosed with endoscopy and 9 (2.4%) were diagnosed with cancer. Of the 411 patients undergoing gastrointestinal endoscopy, 25 (6.1%) had endoscopic findings and 17 (4.1%) had pathologic cancer diagnoses. Conclusion: The training of secretaries and nurses in the delivery of endoscopy appointments can be effective in making ensuring participation, ensuring patient safety, using time more efficiently, and most importantly, not being exposed to possible risks. It can also contribute to reducing unnecessary workload and providing more time for patients. Thus, on patient satisfaction is expected to have a positive effect.